Selective Grazing by a Tropical Copepod (Notodiaptomus iheringi) Facilitates Microcystis Dominance - Leitão, Ewaldo; Ger, Kemal A.; Panosso, Renata (Frontiers in Microbiology, 2018)
Top-down grazer control of cyanobacteria is a controversial topic due to conflicting reports of success and failure as well as a bias towards studies in temperate climates with large generalist grazers like Daphnia. In the tropical lowland lakes of Brazil, calanoid copepods of the Notodiaptomus complex dominate zooplankton and co-exist in high abundance with permanent blooms of toxic cyanobacteria, raising questions for grazer effects on bloom dynamics (i.e., top-down control vs. facilitation of cyanobacterial dominance). Accordingly, the effect of copepod grazing on the relative abundance of Microcystis co-cultured with a eukaryotic phytoplankton (Cryptomonas) was evaluated in a series of six-day laboratory experiments. Grazer effects were tested in incubations where the growth of each phytoplankton in the presence or absence of the copepod N. iheringi was monitored in 1L co-cultures, starting with a 6-fold initial dominance of Cryptomonas by biomass. Compared to the no grazer controls, N. iheringi reduced the growth of both phytoplankton, but Cryptomonas growth was reduced to negative values while Microcystis growth continued positively despite grazers. Hence, in a matter of six days selective grazing by N. iheringi increased the biomass of Microcystis relative to Cryptomonas by an order of magnitude compared to controls, and thus, facilitated the dominance of this cyanobacterium. To account for the potential effect of allelopathy, we performed a secondary experiment comparing the abundance and growth rate of Microcystis and Cryptomonas in single and mixed co-cultures in the absence of grazers. The growth rate of Microcystis was unaffected by the presence or relative abundance of Cryptomonas, and vice versa, indicating no allelopathic effects. Our results suggest that selectively grazing zooplankton may facilitate cyanobacteria blooms by grazing on their eukaryotic phytoplankton competitors in nature. Given that selective grazers predominate zooplankton biomass in warmer waters, grazer facilitation of blooms may be a common but poorly understood regulator of plankton dynamics in a warmer and more eutrophic world.